IMPORTANCE OF DEW AS A REMOVER OF ATMOSPHERIC CATIONS AND ANIONS IN AN URBAN AREA OF SANTIAGO, CHILE - Rubio, Maria (Journal of the Chilean Chemical Society, 2025)
ABSTRACT In an urban commune of Santiago, Chile, a monitoring campaign for dew and PM10 atmospheric particulate matter was implemented during 2022. The pH, conductivity, cation and anion concentrations of dew water, and the water-soluble fraction of PM10, were analyzed. In the water-soluble fraction of PM10, the average cation concentrations were: 4.19 µgm3 for ammonia; 1.40 µgm-3 for calcium; 0.46 µgm-3 for potassium; 0.36 µgm-3 for sodium; and 0.17 µgm-3 for magnesium. In a decreasing order, concentrations were: NH4 ˃ Ca ˃ K ˃ Na ˃ Mg ˃ Zn ˃ Ba ˃ Cu ˃ Mn ˃ Al ˃ As ˃ V. Among anions, the nitrate ion showed concentrations within the 4.49 to 20.09 µgm-3 range. The concentration of the carbonate ion ranged between 0 and 6.7 µgm-3 ; the sulphate ion ranged from 2.65 to 6.13 µgm-3 ; the chloride ion from 2.21 to 3.43 µgm-3 M; the phosphate ion varied between 2.08 and 2.33 µgm-3 ; the nitrite ion between 1.21 and 1.33 µgm-3 ; and the fluoride ion between 0.14 and 0.18. Simultaneously, 60 water dew events were collected during working days, with a total volume of 6465 mL, and 20 events on weekends. This volume was similar to the total level of rainfall in Santiago during 2022 (8217mL). In the dew water, the mean pH was 7.47, and the mean concentrations were: ammonia:13300 µgL-1, calcium: 12040 µgL-1 , potassium: 2600 µgL-1 , sodium 1530 µgL-1 , magnesium: 669 µgL-1 , zinc: 65 µgL-1, manganese: 50 µgL-1 , and copper:19 µgL-1. Among anions, mean concentration values were: chlorides: 8720 µgL-1 ; sulphates: 28938 µgL-1; nitrates: 32538 µgL-1: nitrites: 7556 µgL-1; and carbonates: 14540 µgL-1. Simple linear correlations between cations and anions present in dew water and PM10 showed values of 0.788 and 0.81, indicating a key removing role from the dew water in this city. In Santiago, dew water has a cleansing or removal effect as important as that of rain water